2016
DOI: 10.1111/1471-3802.12363
|View full text |Cite
|
Sign up to set email alerts
|

Factors that explain placement decisions for students with multiple disabilities: findings from national data

Abstract: The Special Education Elementary Longitudinal Study data set was utilised to examine the potential influences on placement decisions for students with multiple disabilities in the US. The sample consisted of 415 students. Specifically, the study investigated whether factors including students’ prior special education experiences, parental involvement, parental expectations and educational risk factors explain the placement of students in classrooms. Results indicate significant relations between the explanator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…Most difficulties are found around PI in regards to the individual educational plan (IEP) and placement in http: //dx.doi.org/10.15405/epsbs.2018.06.70 Corresponding Author: Alina S. Rusu Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 596 appropriate educational frameworks. In practice, parents tend to be more involved both at a local level regarding their own children and on a national level to promote the rights of children with SN in contrast to parents of children with high incidence (Banerjee et al, 2016;Newman, Cameto & Hernandez, 2006). …”
Section: Involvement Of Parents Of Children With Complex Disabilitiesmentioning
confidence: 99%
“…Most difficulties are found around PI in regards to the individual educational plan (IEP) and placement in http: //dx.doi.org/10.15405/epsbs.2018.06.70 Corresponding Author: Alina S. Rusu Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 596 appropriate educational frameworks. In practice, parents tend to be more involved both at a local level regarding their own children and on a national level to promote the rights of children with SN in contrast to parents of children with high incidence (Banerjee et al, 2016;Newman, Cameto & Hernandez, 2006). …”
Section: Involvement Of Parents Of Children With Complex Disabilitiesmentioning
confidence: 99%
“…Browder, Wakeman, Spooner, Ahlgrim-Delzell, and Algozzine (2006) as well as Thurlow, Elliott, and Ysseldyke (2003) indicated that alignment of assessments, instruction, and content standards increase the overall performance of students with and without disabilities. Yet Banerjee et al (2016) indicate that students with extensive needs are frequently taught skills and concepts in isolation which are rarely reiterated enough or connected to overall student learning. Support services alignment with content area instruction should be considered for students with extensive needs.…”
Section: Literacy Instruction For Students With Extensive Support Needsmentioning
confidence: 99%
“…Fenlon et al (2010) found that students' alternative methods of communication frequently result in a lack of understanding or uncertainty of how to incorporate devices into individual or group instruction for both special and general education teachers. In addition, because students with extensive needs frequently work on developing skills that will help them to access daily life as well as academic instruction, they are frequently subject to less content instruction time and increased time with providers working on nonacademic skills in separate or alternative settings (Banerjee, Sundeen, Hutchinson, & Jackson, 2016). Billy's team makes a genuine effort to provide support and instruction to Billy, his general education teacher, and his family who were all initially tentative about using the device.…”
Section: Literacy Instruction For Students With Extensive Support Needsmentioning
confidence: 99%
“…- Banerjee, Sundeen, Hutchinson, and Jackson (2016) found that students who had received early intervention/early childhood services (therefore were in the role of "special needs" student in pre-school years) spent less time in general classrooms at school. -Blum, Gutierrez & Peck (2015) provided a conceptual framework for inclusive education founded on socially valued roles, activities and settings.…”
Section: The Power Of Mind-sets and Expectancies "What One Party Exmentioning
confidence: 99%
“…Although typically used in regard to service design and implementation, SRV is also relevant to families (Osburn, 2006), and can explain the impact of disability on family decisions (Sherwin, 2014). Parents, like everyone else, are subject to the dynamics that SRV outlines, and their expectations have an association with their children's school experiences (Banerjee et al, 2016). Examples of how SRV theory relates to parents' schooling expectations for their children with intellectual disability are presented in the following sections; SRV themes introduced in Table 1 (Chapter Three) that are particularly pertinent to families and to preferences for special schooling will be discussed.…”
Section: Srv and Familiesmentioning
confidence: 99%